Development of Factoring Services in Poland in The Years 2011-2022 - Walkusz, Sandra; Dziadek, Krzysztof (Journal of Finance and Financial Law, 2024)
The purpose of the article. The aim of the article is to analyze the market of factoring services in Poland in the years 2011-2022 and to evaluate the impact of selected macro- and microeconomic factors on the development of factoring in Poland during this period. For the purposes of the study the adopted hypothesis regraded the existence of a positive correlation between the value of factoring turnovers and the gross domestic product; revenues from the sale of products, goods, and services; liabilities arising from deliveries and services; and short-term liabilities from loans and borrowings. Methodology. The sources of data on the factoring services market were statistical data from the Polish Factors Association (PFA) and the Central Statistical Office (CSO). Pearson correlation coefficients were used to measure dependencies. Meanwhile, to examine the significance of the obtained results, the t-Student test statistic was employed. Results of the research. The study results confirm the growing popularity of factoring as a source of financing for economic activities. In the period 2011-2022, the number of financed invoices and the value of receivables purchased by factors increased fourfold. The conducted analysis of correlation coefficients revealed a very strong dependence between the value of factoring receivables and all analyzed economic factors (all coefficients had a value above 0.9). The results of the t-Student test suggest that all these dependencies were statistically significant.